HUBUNGAN PENGETAHUAN IBU DENGAN STATUS GIZI BALITA DI DESA REDANG SEKO KECAMATAN LIRIK - Astri Yuli Yanti; Yopi Wulandhari; Fitriyani Bahriyah (STIKes Al-Insyirah Pekanbaru, 2021)
The body needs the basic foods it needs for growth and health. Nutritional status is a condition in the human body which is the impact of food and the use of nutrients consumed by a person. The purpose of this study was to determine the relationship between knowledge and nutritional status of children under five in Redang Seko Village, Lirik District. The method used is analytic with a cross sectional approach. The sample in this study were mothers and toddlers with a total of 49 people. Data were analyzed by chi square test. The results of the study obtained that knowledge was sufficient (46.9%) and the nutritional status of children under five was normal (83.7%). The results of the chi square statistical test obtained a p-value of 0.001. So it can be concluded that there is a relationship between mothers and the nutritional status of children under five in Redang Seko Village, Lirik District.